Advancing Aptamers as Molecular Probes for Cancer Theranostic Applications—The Role of Molecular Dynamics Simulation. Issue 3 (7th January 2020) - Jeevanandam, Jaison; Tan, Kei Xian; Danquah, Michael Kobina; Guo, Haobo; Turgeson, Andrew
Abstract: Theranostics cover emerging technologies for cell biomarking for disease diagnosis and targeted introduction of drug ingredients to specific malignant sites. Theranostics development has become a significant biomedical research endeavor for effective diagnosis and treatment of diseases, especially cancer. An efficient biomarking and targeted delivery strategy for theranostic applications requires effective molecular coupling of binding ligands with high affinities to specific receptors on the cancer cell surface. Bioaffinity offers a unique mechanism to bind specific target and receptor molecules from a range of non‐targets. The binding efficacy depends on the specificity of the affinity ligand toward the target molecule even at low concentrations. Aptamers are fragments of genetic materials, peptides, or oligonucleotides which possess enhanced specificity in targeting desired cell surface receptor molecules. Aptamer–target binding results from several inter‐molecular interactions including hydrogen bond formation, aromatic stacking of flat moieties, hydrophobic interaction, electrostatic, and van der Waals interactions. Advancements in Systematic Evolution of Ligands by Exponential Enrichment (SELEX) assay has created the opportunity to artificially generate aptamers that specifically bind to desired cancer and tumor surface receptors with high affinities. This article discusses the potential application of molecular dynamics (MD) simulation to advance aptamer‐mediated receptor targeting in targeted cancer therapy. MD simulation offers real‐time analysis of the molecular drivers of the aptamer‐receptor binding and generate optimal receptor binding conditions for theranostic applications. The article also provides an overview of different cancer types with focus on receptor biomarking and targeted treatment approaches, conventional molecular probes, and aptamers that have been explored for cancer cells targeting. Abstract : This article discusses the potential application of molecular dynamics simulation to advance aptamer‐mediated receptor targeting in targeted cancer therapy. The article also provides an overview of different cancer types with focus on receptor biomarking and targeted treatment approaches, conventional molecular probes, and aptamers that have been explored for cancer cells targeting.